Retrospective study of rheumatological patients in a private homoeopathic medical practice - Wassenhoven, Michel Van (British Homeopathic Journal, 1996)
A retrospective study of rheumatological patients seen in a private homoeopathic practice was conducted. 3,555 computerized patient files were surveyed, yielding 99 patients with a primary diagnosis of arthritis. Patient files were analysed by diagnosis, demographic variables and duration of follow-up.Response to treatment, level of similarity, medicines and dilutions prescribed are presented. Forty-three patients were able to stop all conventional medication, most of the treatment failures were in-patients with relatively brief follow-up.Some representative case histories are described.